An H[the sign of infinity] sliding mode observer for Takagi-Sugeno nonlinear systems with simultaneous actuator and sensor faults - Ben Brahim, Ali; Dhahri, Slim; Ben Hmida, Fayçal; Sellami, Anis (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers the problem of robust reconstruction of simultaneous actuator and sensor faults for a class of uncertain Takagi-Sugeno nonlinear systems with unmeasurable premise variables. The proposed fault reconstruction and estimation design method with H[the sign of infinity] performance is used to reconstruct both actuator and sensor faults when the latter are transformed into pseudo-actuator faults by introducing a simple filter.
Keywords: fault reconstruction and estimation; simultaneous faults; H[the sign of infinity] sliding mode observer; uncertain Takagi-Sugeno systems; LMI optimization